Virtual Reality and Consciousness: Specifics of Cultural-Philosophical Research - Abdurazakova, Gaukhar; Abdikalyk, Ainura; Bissenova, Aliya; Kuandykova, Elmira; Sultaniyarova, Anar (Journal of Posthumanism, 2025)
The article discusses the essence and significance of virtual reality, the genesis of formation and its impact on public life and its influence on the formation of consciousness. Virtual reality technology encompasses the software and hardware that make up the entire virtual reality world. Virtual reality was created with the aim of allowing people to know the world in a completely new and harmless way and to give new life to a number of industries through the proposed technologies. XXI century information age. Perhaps even thenat the moment, virtual reality covers the dominant time of human life. The information age has also led to the age of dependence, which unconsciously controls the human mind, opening the way to many opportunities and discoveries in human life. "Virtual reality" has actively penetrated the consciousness of modern society. The fact of the existence of virtual reality is associated both with the use of modern information technologies and with various mental, aesthetic, cultural, semiotic, esoteric processes. The concept of" virtual reality " is widely used to refer to various phenomena. To overcome the uncertainty and diversity of understanding this phenomenon, it is necessary to determine its essence. In short, there is nothing that cannot be done with technology in virtual reality systems. The study of the specifics of virtual reality is determined by the need to clarify the concepts of "virtual", "reality" and "virtual reality", which makes it possible to overcome the uncertainty that has arisen due to various interpretations of this phenomenon, to clearly understand the essence of this phenomenon. The need for research arises from the increased influence of virtual reality on consciousness.